Effect of clonidine as an adjuvant for wound infiltration following caesarean section - M S Nataraj; Sathisha; R M Mohan Kumar (Wolters Kluwer Medknow Publications, 2017)
Context: Local anesthetics provide simple and safe means of postoperative analgesia when used for local infiltration. Role of clonidine as an adjuvant is being increasingly explored because of its peripheral action. Aims: To investigate the analgesic effect of clonidine when added to bupivacaine for wound infiltration following cesarean section. Settings and Design: A prospective, randomized double-blind study was conducted after Institutional Ethical committee approval. Materials and Methods: Sixty American Society of Anesthesiologists (ASA) physical status I or II parturients scheduled for elective cesarean delivery through pfennensteil incision were included after consent. Patients were randomly allocated to two groups; Group B (control group) received 30 ml of 0.25% bupivacaine for wound infiltration and Group C received 3 μg/kg clonidine mixed with 0.25% bupivacaine. Time to first request of analgesia, total tramadol consumption, visual analog scale (VAS) pain scores, sedation, any complications were recorded at 6th hourly interval till 24 hours. Statistical analysis used: Data and perioperative details are summarized as mean ± SD. Statistical analysis for significance was done using two sample unpaired t-test. Results: Demographic and surgical parameters were comparable. Time for first request of analgesia was prolonged in group C (254 ± 26 min vs group B 149 ± 12 min;P < 0.0001), total tramadol consumption was significantly less (P < 0.001), and pain scores were lower (P < 0.001) in clonidine group up to 12 h. Conclusions: Addition of 3 μg/kg of clonidine to 0.25% bupivacaine 30 ml for wound infiltration after cesarean section prolongs the duration of analgesia, reduces opioid consumption, and produces mild sedation without complications.